2022
DOI: 10.12659/msm.937003
|View full text |Cite
|
Sign up to set email alerts
|

Can the Density of Mineralized Dental Tissues (Dentin and Enamel) Be Measured and Compared with 3D Cone Beam Computed Tomography in Cases of Ectodermal Dysplasia?

Abstract: Background Since 3-dimensional cone beam computed tomography (CBCT) started to be used in dentistry, mineral density can now be examined with computer software from the data on the images obtained. Detailed and clear images at different slice intervals can be obtained with CBCT, and mineral density can be measured from the image data on a computer with a Hounsfield unit (HU) scale. In addition to the broad opportunities presented by CBCT, this feature has presented a wider perspective to researche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…Previous studies of extracted teeth using microcomputed tomography showed uneven distribution of enamel and dentin densities in different areas of the tooth [ 14 ]. Yavuz et al [ 15 ] confirmed this pattern in a mixed-age population using CBCT in their study. However, the densities of enamel and dentin in their study were lower than the average values obtained during our study.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Previous studies of extracted teeth using microcomputed tomography showed uneven distribution of enamel and dentin densities in different areas of the tooth [ 14 ]. Yavuz et al [ 15 ] confirmed this pattern in a mixed-age population using CBCT in their study. However, the densities of enamel and dentin in their study were lower than the average values obtained during our study.…”
Section: Discussionsupporting
confidence: 62%
“…Information about the range of Hounsfield values for healthy teeth tissues could become an additional tool in assessing dental health, age estimation [ 12 ], and anatomy [ 13 ] and could be used, among other data, for subsequent machine learning [ 14 ]. The results of earlier studies do not provide convincing data on the range of Hounsfield values for healthy dental tissues in children of a certain age group [ 15 16 ]. Our study is aimed at establishing the Hounsfield values of dental tissue density in children in the same age group.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Previous studies of extracted teeth using micro-computed tomography showed an uneven distribution of enamel and dentin density in different areas of the tooth. [13] Yavuz [14] confirmed this pattern in a mixed age population using CBCT in their study. However, the values of enamel and dentine density in their study were lower than the average values obtained during our study.…”
Section: Textsupporting
confidence: 61%
“…[13] The results of earlier studies do not provide convincing data on the range of HU for healthy dental tissues in children of a certain age group. [14,15] Our study is aimed at establishing Hounsfield values for dental tissues in children of a certain age group.…”
mentioning
confidence: 99%
“…Some types of ectodermal dysplasia are suitable for genetic testing, which can confirm the diagnosis and help with genetic counseling [ 5 ]. Others have attempted to use cone-beam computed tomography to assess the viability and usefulness of measuring the mineralization of dental tissues in the ectodermal dysplasia and control groups [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%